COMPREHENSIVE ASSESSMENT ON THE MARKETING OPPORTUNITIES IN A RURAL COMMUNITY AT KIORAO, KIBAWE, BUKIDNON - Bonifacio, Michael Bonn A.; Sudaria, Ma. Concepcion C. (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
The Municipality of Kibawe is part of the 3rd congressional district in the province of Bukidnon, and was considered as GIDA (Geographically Isolated and Disadvantage Areas) as evidenced of their high poverty incidence among its residents. With the benefits brought by entrepreneurial activities to economic growth and mitigating occurrence of poverty that this research was conducted to validate the theory. The study aimed to determine the level of businesses and entrepreneurs’ marketing practices, and how their strategies and practices are associated with the existing capabilities provided by government and to the community’s satisfaction to implemented marketing strategies. It surveyed 128 household representatives at barangay Kiorao, in the Municipality of Kibawe. The research design was descriptive-correlation method and the statistical tools used where mean, and Pearson r correlation coefficient. Results revealed that place, people management and promotional marketing strategies are evidently practiced, product and price strategies are also observed but at a lesser extent. There were minimal business activities relating to product and pricing strategies. When associated with enterprise capabilities, the people, place and distribution, and promotional strategies were positively correlated at 0.05 and 0.01 level of significance. Respondent were satisfied with the marketing capabilities exhibited by these enterprises used of available resources, adoption of marketing practices, and appreciation of the importance of these aforementioned strategies for the success of the sustainability of their respective endeavor.